Impak pameran dan perkhidmatan pandu lalu terhadap pinjaman buku baharu: kajian berasaskan Return on Investment (ROI) - Ibrahim, Shamsudin; Yusof, Rosnah; Ishak, Azmah; Sidek, Harith Faruqi; Sukarno, Norliah; Mohd Rohani, Rohalia; Ahmad Hosaini, Nor Hamsiah; Awang, Fatimah Kamilah; Sahamir, Azhari; Othman, Nor Ilyah; Jasman, Liyana; Mhd Redza, Mohd Syamrooz Kamal (Persatuan Pustakawan Malaysia, 2016)
The Library has purchased 10,050 copies of printed books for UKM researchers from 2009 to 2013. Nevertheless, the study found only 4,864 (48.4%) of books were borrowed. This problem should be overcome due to the fact that the estimated cost of books purchasing is RM8.72 million compared to the value of the books that were borrowed (RM4.5 million). A preliminary study was conducted by the Management Quality Improvement Team (QIT) with regards to borrowing transactions using Return on Investment (ROI) and Cost Benefit Ratio (CBR) methods. Several suggestions on how to increase books circulation were presented by the Management QIT to the Library. Two suggestions were implemented by the Innovative and Creative Group (ICG) KLIK in 2014/2015 which included new books display and Drive-Thru@PTSL service. The study has proved that new books display and Drive-Thru@PTSL service have increased the borrowing transaction rate from 1.6% up to 46.8% in nine months.